Video Endoscopic Inguinal Lymphadenopathy (VEIL): An Experience from a Single Institute Study - Dhangar, Dr. Sanjay P. (SP'z Series New Insights on Urology and Urological Research Part I, 2022)
VEIL is a novel and appealing solution that duplicates the open procedure. It decreases post-operative pain, allowing for a quicker recovery and lower total morbidity. We describe the surgery and its complications, as well as our early experience with this treatment. We included a total of 6 procedures involving penile carcinoma of moderate to high grade with no palpable inguinal lymph nodes who were at high risk of inguinal metastases and were treated with VEIL. We found no cutaneous complications, two patients with localised lymphocoele, and one patient with surgical emphysema. Overall morbidity was lower, and there was no mortality. In penile cancer patients with non-palpable or low-volume palpable inguinal disease, VEIL is a viable minimally invasive method for radical inguinal dissection. Newer studies with a larger number of patients and longer follow-up times may be able to confirm the oncological safety and potential decreased morbidity of this unique technique.